Stretch‐induced Ca2+ independent ATP release in hippocampal astrocytes. (6th April 2018) - Xiong, Yingfei; Teng, Sasa; Zheng, Lianghong; Sun, Suhua; Li, Jie; Guo, Ning; Li, Mingli; Wang, Li; Zhu, Feipeng; Wang, Changhe; Rao, Zhiren; Zhou, Zhuan
Abstract : Key points: Similar to neurons, astrocytes actively participate in synaptic transmission via releasing gliotransmitters. The Ca 2+ ‐dependent release of gliotransmitters includes glutamate and ATP. Following an 'on‐cell‐like' mechanical stimulus to a single astrocyte, Ca 2+ independent single, large, non‐quantal, ATP release occurs. Astrocytic ATP release is inhibited by either selective antagonist treatment or genetic knockdown of P2X7 receptor channels. Our work suggests that ATP can be released from astrocytes via two independent pathways in hippocampal astrocytes; in addition to the known Ca 2+ ‐dependent vesicular release, larger non‐quantal ATP release depends on P2X7 channels following mechanical stretch. Abstract: Astrocytic ATP release is essential for brain functions such as synaptic long‐term potentiation for learning and memory. However, whether and how ATP is released via exocytosis remains hotly debated. All previous studies of non‐vesicular ATP release have used indirect assays. By contrast, two recent studies report vesicular ATP release using more direct assays. In the present study, using patch clamped 'ATP‐sniffer cells', we re‐investigated astrocytic ATP release at single‐vesicle resolution in hippocampal astrocytes. Following an 'on‐cell‐like' mechanical stimulus of a single astrocyte, a Ca 2+ independent single large non‐quantal ATP release occurred, in contrast to the Ca 2+ ‐dependent multiple small quantal ATP release in a chromaffin cell. The mechanical stimulation‐induced ATP release from an astrocyte was inhibited by either exposure to a selective antagonist or genetic knockdown of P2X7 receptor channels. Functional P2X7 channels were expressed in astrocytes in hippocampal brain slices. Thus, in addition to small quantal ATP release, larger non‐quantal ATP release depends on P2X7 channels in astrocytes. Key points: Similar to neurons, astrocytes actively participate in synaptic transmission via releasing gliotransmitters. The Ca 2+ ‐dependent release of gliotransmitters includes glutamate and ATP. Following an 'on‐cell‐like' mechanical stimulus to a single astrocyte, Ca 2+ independent single, large, non‐quantal, ATP release occurs. Astrocytic ATP release is inhibited by either selective antagonist treatment or genetic knockdown of P2X7 receptor channels. Our work suggests that ATP can be released from astrocytes via two independent pathways in hippocampal astrocytes; in addition to the known Ca 2+ ‐dependent vesicular release, larger non‐quantal ATP release depends on P2X7 channels following mechanical stretch.